2017
DOI: 10.1080/1061186x.2017.1363212
|View full text |Cite
|
Sign up to set email alerts
|

Silk nanoparticles: proof of lysosomotropic anticancer drug delivery at single-cell resolution

Abstract: Silk nanoparticles are expected to improve chemotherapeutic drug targeting to solid tumours by exploiting tumour pathophysiology, modifying the cellular pharmacokinetics of the payload and ultimately resulting in trafficking to lysosomes and triggering drug release. However, experimental proof for lysosomotropic drug delivery by silk nanoparticles in live cells is lacking and the importance of lysosomal pH and enzymes controlling drug release is currently unknown. Here, we demonstrate, in live single human bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 46 publications
(69 reference statements)
3
54
0
Order By: Relevance
“…Overall, all the silk nanoparticles generated were highly crystalline and essentially identical with respect to their secondary structure to nanoparticles we have previously reported. 8,9 Morphological assessment by electron microscopy indicated that the total ow rate and the ow rate ratio were the key parameters that inuenced the particle appearance (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, all the silk nanoparticles generated were highly crystalline and essentially identical with respect to their secondary structure to nanoparticles we have previously reported. 8,9 Morphological assessment by electron microscopy indicated that the total ow rate and the ow rate ratio were the key parameters that inuenced the particle appearance (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, silk nanoparticles are emerging as interesting carriers for drug delivery and are now oen proposed for solid tumor drug targeting. [7][8][9][10] Silk nanoparticles can be rened-for example, by surface decorating with polyethylene glycol (PEG)to further tailor their performance by improving their colloidal stability and tuning their immune recognition. 8,11 Both native and PEGylated silk nanoparticles have demonstrated high drug loading efficacy, pH-dependent drug release, and selective degradation by protease enzymes as well as by ex vivo lysosomal enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Once inside the cells, the payloads on silk fibroin nanoparticles can also be activated within lysosomes (i.e., lysosomotropic drug delivery) by the low pH and the proteolytic enzymes of lysosomes, given the correct intracellular trafficking of the nanoparticles . The lysosomal environment not only triggers drug release but is also the site of silk fibroin nanoparticle degradation .…”
Section: Preclinical Use Of Silk—the Futurementioning
confidence: 99%
“…Nanomaterials can act as the carrier for conventional drugs by transporting drugs or proteins through lysosomes such as AuNRs conjugated with Naja kaouthia protein toxin 1 (NKCT1) (one of the snake toxin protein) [191], silk NPs conjugated with doxorubicin (anti-cancer drugs) [192], and AgNPs conjugated with salinomycin (killing agent for cancer stem cells) [193]. These nanomaterials can maximize drug delivery to reach the lysosome easily, and, subsequently, kill the cancer cells from leukemia [191], breast cancer [192], and ovarian cancer [193]. The "small size" of NPs, which is one of the typical characteristics, can be used to penetrate obstacles that conventional drugs cannot cross, especially the blood brain barrier (BBB) [194].…”
Section: Np-induced Proton Sponge Effect Through Ion Channels In the mentioning
confidence: 99%